Rational Witches? The Agency of Women on Trial for Supernatural Crimes in Early Modern Ghent - Roelens, Jonas (Early Modern Low Countries, 2025)
This essay examines the defence strategies of women accused of witchcraft in early modern Ghent, focusing on their agency within restrictive societal frameworks. Cases like that of Adriaene Schepens illustrate how accused women refuted supernatural accusations through rational explanations that exploited societal and gendered expectations. Rather than relying solely on emotional pleas, these women employed logical arguments and constructed personas that undermined the charges against them. Analysing trial records reveals how gender stereotypes were strategically used to appear non-threatening, reflecting broader social and cultural dynamics. The findings challenge traditional legal and demonological perspectives, emphasising the resilience and agency of accused women. The article advocates for an accessible database of accused individuals to trace defence strategies across cases, enriching the historiography of witchcraft in the Southern Low Countries and advancing understanding of gendered interactions in early modern legal history.